Does the green credit policy promote the technological innovation of clean energy enterprises? Empirical evidence from China - Xuesong Gu; Zehua Tian (Frontiers in Energy Research, 2023)
The technological innovation of clean energy enterprises is conducive to the transformation of energy structure, and the green credit policy is just a potential opportunity for clean energy enterprises to seek financing convenience. This paper constructs quasi-natural experiments during two different lengths of period (2008–2015 and 2008–2020) based on the 2012 Green Credit Guidelines, selecting a group of A-share listed clean energy enterprises and non-clean energy enterprises as samples. The aim is to examine the impact of green credit policies on the technological innovation of clean energy enterprises. This paper further conducts mechanism tests as well as heterogeneity analysis on the basis of the results. The results show that green credit policies can promote technological innovation for clean energy enterprises, and this effect is reinforced with the accumulation of years following policy implementation. The mechanism test indicates that green credit policies affect the level of technological innovation of clean energy enterprises through credit cost and financing constraints. The heterogeneity analysis demonstrates that the impact of green credit policies is more significant in the non-state-owned enterprises and economically developed regions. The results provide insights for the promotion of green credit policy and the ultimate transformation of China’s energy structure, thus providing reference for developing countries and emerging economies. The formulation of green credit policy should take into account the long-term effect, reduce the burden of enterprises from the perspective of credit cost and financing constraints, and also expand the influence of the policy in state-owned enterprises and underdeveloped areas.